HOW TO BRIDGE THE GAP BETWEEN THE RESULTS OF PSYCHOLOGICAL RESEARCH AND THE REALITY OF EVERYDAY CLASSROOM LEARNING - Kovalčíková, Iveta (European Scientific Journal, ESJ, 2014)
The article discusses a systematic research approach to the transformation of the educational system in the midst of curricular reform in Slovakia. During this period of curricular reform in Slovakia, experts consider what the features of an ideal school system and the goals of their reforming efforts should be. This article argues that: reforming tendencies should not ignore the results of the latest neuropsychological and cognitive-psychological research into learning and refers to the growing divide between the results of neurological and psychological research and their application within the classroom. The author describes an example of interdisciplinary research involving expertise in four different academic fields aimed at restructuring the curriculum for teacher trainees. The main goals of the research are: to analyze the principles of cognitive education; to create preconditions for its legal implementation into practice; to justify the position of cognitive education as a key principle of education; to create a supportive environment for its development starting with a paradigmatic change of teacher training. Both on the level of basic and of applied research, the research team aims to contribute to the understanding of what is meant by the ability to learn and to identify part of the spectrum of processes which make up this ability.